Pengaruh Tinggi Muka Air Terhadap Deformasi Tanah Terlikuefaksi - A. Beddu; R. Rahainun; I. Fadliah; A. Rahayu; H. Setiawan (Civil Engineering Department, Tadulako University, 2022)
Liquefaction occurs in saturated loose sandy soils that experience an increase in pore water pressure due to the propagation of earthquake waves to the ground surface. This phenomenon raises various questions such as how the groundwater level can affect the occurrence of liquefaction events at different earthquake strengths. The purpose of this study was to determine the effect of groundwater level on liquefaction-prone soils at different seismic peak acceleration values and the effect of relative density (Dr) values on liquefaction-prone soils with variations in groundwater level and earthquake acceleration. In this study, a sample of Jono Oge sand soil was used from the occurrence of liquefaction that met the gradation criteria. The soil was separated through the #8 sieve and retained #100. The modeling technique is carried out with several variables such as the ratio of groundwater level (Hw/Hs) of 25%, 50%, 75%, and 90%, relative density (Dr) 30%-40% and 40%-50%, and at different peak accelerations of 0.3g and 0.4g. The modeling test uses a sieve shaker for earthquake vibrations.. The results of the study show that the difference in groundwater level affects the subsidence of liquefied soil where the settlement will be accure greater in the ratio of the groundwater level (Hw/Hs) and the peak acceleration is greater and vice versa, the difference in relative density (Dr) also affects the magnitude of the the settlement where the lower the Dr value for Hw/Hs and the greater the peak acceleration, the greater the settlement will be occure.